2011
DOI: 10.1002/jhm.955
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the interpretation of chest radiographs for the diagnosis of pneumonia in children

Abstract: BACKGROUND:Although chest radiography is commonly used to establish the diagnosis of pneumonia in children, the reliability of radiographic findings among radiologists is not well described.OBJECTIVE:We sought to evaluate the inter‐rater and intra‐rater reliability of radiographic features commonly described by radiologists in childhood pneumonia.METHODS:Prospective case‐based study. One hundred and ten radiographs of children evaluated in a pediatric emergency department for suspicion of pneumonia were interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 19 publications
4
83
3
1
Order By: Relevance
“…Ultrasound has several advantages over other imaging modalities: it can be performed at POC, it is feasible and less costly than chest radiography, it is less affected by movement or crying than other imaging modalities, it can be done in sleeping children, 35 and it is free of ionizing radiation. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Although ultrasound performed by non-radiologists is controversial, it has become a useful tool for physicians, emergency medicine doctors, and intensivists. 44 Lung ultrasound involves scanning a child in the anterior, lateral, and posterior areas of each hemithorax.…”
Section: Advances In Radiological Diagnosismentioning
confidence: 99%
“…Ultrasound has several advantages over other imaging modalities: it can be performed at POC, it is feasible and less costly than chest radiography, it is less affected by movement or crying than other imaging modalities, it can be done in sleeping children, 35 and it is free of ionizing radiation. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Although ultrasound performed by non-radiologists is controversial, it has become a useful tool for physicians, emergency medicine doctors, and intensivists. 44 Lung ultrasound involves scanning a child in the anterior, lateral, and posterior areas of each hemithorax.…”
Section: Advances In Radiological Diagnosismentioning
confidence: 99%
“…In epidemiological studies, the chest radiograph remains a major criterion in classifying pneumonia [3], [4]. However, variability in its interpretation for the diagnosis of pneumonia in children is a recognised problem [5]. It has been suggested that if radiologists follow the standardised World Health Organization (WHO) radiological definitions of pneumonia [3], this would allow more accurate comparative data in epidemiological studies for assessment of the impact of pneumococcal vaccination [4].…”
Section: Introductionmentioning
confidence: 99%
“…It exposes patients to ionizing radiation, and ill children with suspected pneumonia may receive multiple CXRs, posing a small increased risk of cancer later in life. [2][3][4] Lung ultrasonography (LUS) has several potential advantages over CXR. Compared with CXR, LUS does not expose the child to ionizing radiation, when used to address specific diagnostic questions requires minimal training for the provider, and can be performed at the point of care.…”
mentioning
confidence: 99%